2021
DOI: 10.1016/j.isci.2021.102786
|View full text |Cite
|
Sign up to set email alerts
|

Motor and sensory cortical processing of neural oscillatory activities revealed by human swallowing using intracranial electrodes

Abstract: Swallowing has two aspects; sensory input and motor outputPhase-amplitude coupling showed differences of motor and sensory neural processing Coupling between the a and high g band occurred before motor-related high g activities Coupling between the q and high g band occurred during sensory-related high g activities

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
2
6
0
Order By: Relevance
“…In this study, ISA-HFA PAC increased before the increase in HFA occurred, and this profile that PAC precedes HFA increasing is also reported in previous studies related to motor-related physiological PAC 25 , 26 . A hold-and-release model was proposed, which indicated that physiological coupling restricted the HFA and attenuation of the coupling releases the HFA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, ISA-HFA PAC increased before the increase in HFA occurred, and this profile that PAC precedes HFA increasing is also reported in previous studies related to motor-related physiological PAC 25 , 26 . A hold-and-release model was proposed, which indicated that physiological coupling restricted the HFA and attenuation of the coupling releases the HFA.…”
Section: Discussionsupporting
confidence: 90%
“…These pathological PACs are usually accompanied by ictal HFA, whereas physiological PACs that are involved in motor-related HFAs (i.e., high γ band) appear before HFA increases 25 , 26 . Physiological PAC precedes physiological HFA; however, whether a preceding seizure-related PAC can be observed before ictal HFA appears is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The HFA power is strongly correlated with the neural firing rate (Ray et al, 2008), and, in animal studies, neural spiking was found to be locked to the trough of α oscillations (Haegens et al, 2011). In a previous study of physiological PAC, high gamma amplitude during high PAC values peaked around the trough of α oscillations (Hashimoto et al, 2021c, Yanagisawa et al, 2012. Moreover, in a study of pathological PAC related to epilepsy, the HFA amplitude during high PAC was time-locked to the trough of lower-frequency oscillations (Ibrahim et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…PAC has been observed in both physiological and pathological neural processing. The former includes hand movement (Yanagisawa et al, 2012), swallowing (Hashimoto et al, 2021c) and somatosensory processing (Lakatos et al, 2008), and the latter includes epileptic seizures (Hashimoto et al, 2020b, 2021b, Iimura et al, 2018, and Parkinson's disease (de Hemptinne et al, 2015). It was reported that ictal HFA amplitudes are coupled with δ (Iimura et al, 2018, Nariai et al, 2011, θ (Hashimoto et al, 2021b, Ibrahim et al, 2014, and α (Ibrahim et al, 2014) phases, while β-HFA coupling has been reported as a useful marker for seizure detection (Edakawa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation